K otázke racionality sebausmrtenia - Spodniak, Stanislav (Filosoﬁcký časopis)
In one of the arguments from his book Obrana asistované smrti (In Defense of Assisted Dying), Tomáš Hříbek argues in favor of the position that suicide can be an instance of rational action under certain circumstances. He proceeds from the criterion of rationality, according to which rational action is that which is advantageous for the individual actor. The aim of this article is to point out that, on the basis of the criterion of rational action in question, suicide cannot in fact be judged to be either a rational or an irrational act. The reason lies in the impossibility of comparing and evaluating whether it is more advantageous for a person to have a life that provides him or her with a certain amount of good, or to not exist. The attempt to make such a comparison leads to a categorical fallacy.